Microbial regulation of GLP-1 and L-cell biology - Thomas U. Greiner; Fredrik Bäckhed (Elsevier, 2016)
Background: The gut microbiota is associated with several of metabolic diseases, including obesity and type 2 diabetes and affects host physiology through distinct mechanisms. The microbiota produces a vast array of metabolites that signal to host cells in the intestine as well as in more distal organs. Scope of review: Enteroendocrine cells acts as 'chemo sensors' of the intestinal milieu by expressing a large number of receptors, which respond to different metabolites and nutrients, and signal to host by a wide variety of hormones. However, enteroendocrine cells differ along the length of the gut in terms of hormones expressed and receptor repertoire. Also, the microbial ecology and dietary substrates differ along the length of the gut, providing further evidence for unique functions of specific subpopulations among enteroendocrine cells. Here we will review how the gut microbiota interacts with L-cells in the small and large intestine and the resulting effects on the host. Major conclusions: Microbial metabolites can be sensed differently by specific subpopulations of enteroendocrine cells. Furthermore, hormones such as GLP-1 can have different functions when originating from the small intestine or colon. This article is part of a special issue on microbiota.